Bank return heterogeneity, do governance, sentiment, and uncertainty matter? - Syed Faisal Shah; Mohamed Al-Baity (Cogent Economics & Finance, 2022)
This paper examined the impacts of; investor sentiment, governance, and uncertainty on bank stock returns in the Middle East and North Africa (MENA) and Gulf Cooperation Council (GCC) region countries. The sample consisted of 173 conventional and Islamic banks based in the MENA region and 68 conventional and Islamic banks based in the GCC region from 2010-2020. Also, this study employed the Two-step system Generalized Method of Moments (GMM) estimator. The selection of this estimator prevented endogeneity issues related to the variables used in this study. This research found that individual sentiment and uncertainty negatively affected bank stock returns while governance positively influenced bank stock returns. The regression coefficients from the interaction of the governance indicators and conventional banks variable showed a positive and significant effect on bank stock returns in the MENA region, except for the interaction of the rule of law and voice and accountability in conventional banks, showing a negative effect. The GCC countries showed similar results. However, the outcomes were insignificant. Regarding the control variables, the loan ratio and inflation were negative, and bank size and the GDP showed positive and significant effects on bank stock returns throughout all models, excluding the loan ratio and bank size in the GCC region. Overall, the banking sectors of the MENA region countries were sensitive to; investor sentiment, uncertainty, and country-level governance indicators.
Keywords: 330; governance; Investor sentiment; MENA; stock return; uncertainty